Minimizers for a one-dimensional interaction energy. (March 2022) - Frank, Rupert L.
Abstract: We solve explicitly a certain minimization problem for probability measures in one dimension involving an interaction energy that arises in the modeling of aggregation phenomena. We show that in a certain regime minimizers are absolutely continuous with an unbounded density, thereby settling a question that was left open in previous works.